Reunión de trabajo con delegados de la Escuela de Policía y del Comando de Policía de la Subzona Bolívar - Llivi Ruilova, Danny Vicente (2023)
Engineer Gray Barragán Aroca, coordinator of the Disaster Risk Engineering degree at the Faculty of Health and Human Sciences, held a working meeting with delegates from the Police School and the Police Command of the Bolívar Subzone, the The purpose of the meeting was to obtain support to provide them with a teacher for the incident command subject, a class taught at the Police School; In response to the request, the material and equipment have already been prepared to teach the classes; They also want the Police to be considered as a place for students to carry out pre-professional practices, gathering information on risks, threats and vulnerabilities in the locality. (D.LL)